Analysis of styrene maleic acid alternating copolymer supramolecular assemblies in solution by small angle X-ray scattering. (February 2019) - Brady, Nathan G.; Qian, Shuo; Bruce, Barry D.
Graphical abstract: Highlights: Styrene maleic acid copolymer supramolecular assemblies are influenced by sample conditions. SAXS reveals significant intermolecular repulsive forces between supramolecular assemblies. Diverse styrene maleic acid formulations exhibit varying tolerances to pH and temperature. Abstract: Over the past decade, Styrene Maleic Acid alternating copolymers (SMA) have gained interest as an alternative to detergent solubilization for the isolation of integral membrane proteins. The formation of SMA lipid particles (SMALPs) presents a novel opportunity to isolate the proximal membrane environment, encompassing and throughout membrane proteins in vitro . Neither the organization or structure of SMAs in an aqueous buffer nor the mechanism by which SMA transforms the membrane bilayer into a SMALP is known. This study investigates the shape and size of diverse SMA polymer complexes/aggregates in solution at various pH, ionic strength, SMA concentration and temperature, analyzed by small angle X-ray scattering. It is clear that SMAs of differing physicochemical properties (styrene to maleic acid ratio, length of copolymer fragments and functionalization) display highly variable sizes/shapes in solution over a range of environmental conditions. The SMA supramolecular aggregates exhibit similar prolate ellipsoidal geometry of varying size, dependent on the degree of hydrophobicity of the SMA copolymer. At elevated temperature, particles composed of SMAs enriched in styrene increase in both radius of gyration and maximum particle diameter. Interestingly, we observe a correlation between the SMALP dimensions and that of native membranes. Future work will investigate if there may be a complimentary relationship between SMA aggregate dimensions and bilayer thickness (and/or protein transmembrane domain thickness), similar to what has been observed for tandem facial amphiphiles.